Promoted room temperature NH3 gas sensitivity using interstitial Na dopant and structure distortion in Fe0.2Ni0.8WO4 - Lee, Jong Hyun; Lee, Seung Yong; Choi, Myung Sik; Lee, Kyu Hyoung (Frontiers in Chemistry, 2024)
The demand for gas-sensing operations with lower electrical power and guaranteed sensitivity has increased over the decades due to worsening indoor air pollution. In this report, we develop room-temperature operational NH3 gas-sensing materials, which are activated through electron doping and crystal structure distortion effect in Fe0.2Ni0.8WO4. The base material, synthesized through solid-state synthesis, involves Fe cations substitutionally located at the Ni sites of the NiWO4 crystal structure and shows no gas-sensing response at room temperature. However, doping Na into the interstitial sites of Fe0.2Ni0.8WO4 activates gas adsorption on the surface via electron donation to the cations. Additionally, the hydrothermal method used to achieve a more than 70-fold increase in the surface area of structure-distorted Na-doped Fe0.2Ni0.8WO4 powder significantly enhances gas sensitivity, resulting in a 4-times increase in NH3 gas response (Rg/Ra). Photoluminescence and XPS results indicate negligible oxygen vacancies, demonstrating that cation contributions are crucial for gas-sensing activities in Na-doped Fe0.2Ni0.8WO4. This suggests the potential for modulating gas sensitivity through carrier concentration and crystal structure distortion. These findings can be applied to the development of room-temperature operational gas-sensing materials based on the cations.